The Effects Of Globalization On The National Sovereignty Of Countries - حسون محمد; حسن أنس (Latakia University Journal - Economic and Legal Sciences Series, 2021)
With the emergence of the first signs of the phenomenon of globalization, the pillars of the nation-state as the central actor in international relations began to shake little by little, given the profound transformations that accompanied this phenomenon at various levels, in addition to the emergence of new actors on the international scene, who are competing with the state in managing its basic functions. Accordingly, countries are facing an existential challenge with regard to their basic functions, and the Chinese experience has constituted a unique model regarding the phenomenon of globalization, as it did not engage in it on the basis of the traditional Western view, but rather chose to adopt the most prominent manifestations of political globalization such as joining the World Trade Organization and activating its role in international organizations, especially nations. The United States as a permanent member of the Security Council, as well as the economic manifestations that led China to openness, investment and the strengthening of strategic partnerships with countries on the principle of interdependence, and accordingly the results of the Chinese experience were largely satisfactory, as it was no longer closed to itself and engaged in globalization while preserving its national sovereignty Both.